2002
DOI: 10.1053/joca.2002.0850
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis reveals the involvement of beta-2 microglobulin (B2M) in human osteoarthritis

Abstract: These results indicate that B2M is highly expressed in OA cartilage and synovial fluid compared to normal, and suggest that B2M may have effects on chondrocyte function that could contribute to OA pathogenesis. Published by Elsevier Science Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 35 publications
1
36
1
1
Order By: Relevance
“…Results from a recent study indicated that B2M was highly expressed in OA cartilage compared to normal and it may have a role in OA pathogenesis [20]. In this study, although B2M levels in OA were significantly higher those found in normal synovial fluid, there was no significant difference in B2M levels between the different OA stages according to a method grading OA severity at arthroscopy.…”
Section: Discussioncontrasting
confidence: 60%
“…Results from a recent study indicated that B2M was highly expressed in OA cartilage compared to normal and it may have a role in OA pathogenesis [20]. In this study, although B2M levels in OA were significantly higher those found in normal synovial fluid, there was no significant difference in B2M levels between the different OA stages according to a method grading OA severity at arthroscopy.…”
Section: Discussioncontrasting
confidence: 60%
“…Taken together these results indicate that MMP2 and PCOLCE levels are connected to each other possibly due to a protective feedback loop. B2M has previously been proposed to be involved in OA pathogenesis as B2M is expressed in OA cartilage and may influence chondrocyte gene expression as well as inhibit proliferation of chondrocytes [39]. The medially up-regulated B2M levels found in the LM scored individual could potentially balance the proliferative stress signals that may be initiated by normal joint usage and/or be the early response to a low grade OA and thus a potential early marker of OA.…”
Section: Discussionmentioning
confidence: 99%
“…FSTL1 has been demonstrated to be correlated to the severity of OA disease as well as CHI3L1 [43-45]. SPARC and B2M are correlated to OA while the IGFBP7 has not been correlated to OA previously [30,39,46]. IGFBP4 is suggested to inhibit the canonical Wnt signaling pathway, which makes elevated levels of IGFBP4 on the medial side in the LM scored specimen an interesting finding as stimulated Wnt signaling is known to be involved in OA pathogenesis [47-50].…”
Section: Discussionmentioning
confidence: 99%
“…27 DNA microarray has revealed 20 genes that are regulated by beta-2 microglobulin in osteoarthritic chondrocytes. 28 Lorenz et al 29 used a combinatorial analysis of proteome and transcriptome to compare rheumatoid arthritis and OA patients, and characterized each pathology by evaluation of each approach.…”
Section: O S T E O a R T H R I T I S P A T H O L O G Ymentioning
confidence: 99%